Evaluative Survey of the Implementation of Curriculum 2013 for The English Subject in High School of South Buton District - Kosam, Darussalam; Hardyanto, Wahyu; Haryono, Haryono (Innovative Journal of Curriculum and Educational Technology, 2018)
Curriculum evaluation needs to be carried out to examine the achievements of the program, supporting factors for the implementation of Curriculum 2013. This study investigated the implementation of Curriculum 2013 in high school English learning in South Buton District. This Evaluative study uses CIPP (Context, Input, Process, and Product) evaluation, model. The results showed that (1) Context (school environment) consisting of the book condition, teacher's understanding of Curriculum 2013 and Curriculum 2013 training had been fulfilled in South Buton district high school related to the implementation of Curriculum 2013, (2) Input (facilities and infrastructure) South Buton is include in the good criteria with percentage of 78%, (3) Process (learning process) which consists of Preliminary Activities, management of learning, application of learning approaches/models, implementation of assessment and closing activities include in good implemented criteria with percentage of 70%, (4) product (student response in learning and learning outcomes), most student responses in learning process is in very good criteria with percentage of 83%. On aspects of spiritual and social attitudes (CC-1 and CC-2), knowledge and skills (CC-3 and CC-4) also achieve the minimum completeness criteria, namely B (66-70). Based on the results, the implementation of Curriculum 2013 in South Buton district high school in terms of CIPP has been well implemented. The result of the evaluation study especially in curriculum evaluation would be beneficial for the improvement and the development of Curriculum 2013.